Gender and COVID-19 : What Have We Learnt, One Year Later? - De Paz Nieves, Carmen; Gaddis, Isis; Muller, Miriam (World Bank, Washington, DC, 2021)
One year into the COVID-19 pandemic, this paper takes stock of new data and analysis to provide an up-to date picture of how women and men have been affected differently in terms of endowments, economic conditions, and agency. With regards to health outcomes, men have suffered a disproportionate burden of COVID-19 mortality, and more men than women were diagnosed with COVID-19. On the other hand, the disruptions in service provision have worsened reproductive health outcomes in several countries. In terms of education, data is scarce but there is no evidence for the hypothesis that families redirected scarce resources to prioritize education of boys over girls. However, girls report having taken on the additional care burden to a larger extent than boys, with potential impacts on their learning time. In terms of labor market consequences, women were more likely than men to stop working and have borne the brunt of the increase in the demand for care work. Businesses with female top managers have also experienced disproportionately more negative impacts. Finally, with respect to voice and agency, the risk of violence has increased for women and girls, especially intimate partner violence. In addition, women have been under-represented in decision-making on COVID-19 and, in some contexts, disadvantaged in access to critical information. The paper concludes with highlighting the importance of collecting sex-disaggregated data to understand the gender-differentiated impacts of the pandemic.